The maize glossy13 gene, cloned via BSR-Seq and Seq-Walking encodes a putative ABC transporter required for the normal accumulation of epicuticular waxes - Li, Li; Li, Delin; Liu, Sanzhen; Ma, Xiaoli; Dietrich, Charles R.; Hu, Heng-Cheng; Zhang, Gaisheng; Liu, Zhiyong; Zheng, Jun; Wang, Guoying; Schnable, Patrick S. (My University, 2013)
Aerial plant surfaces are covered by epicuticular waxes that among other purposes serve to control water loss. Maize glossy mutants originally identified by their “glossy” phenotypes exhibit alterations in the accumulation of epicuticular waxes. By combining data from a BSR-Seq experiment and the newly developed Seq-Walking technology, GRMZM2G118243 was identified as a strong candidate for being the glossy13 gene. The finding that multiple EMS-induced alleles contain premature stop codons in GRMZM2G118243, and the one knockout allele of gl13, validates the hypothesis that gene GRMZM2G118243 is gl13. Consistent with this, GRMZM2G118243 is an ortholog of AtABCG32 (Arabidopsis thaliana), HvABCG31 (barley) and OsABCG31 (rice), which encode ABCG subfamily transporters involved in the trans-membrane transport of various secondary metabolites. We therefore hypothesize that gl13 is involved in the transport of epicuticular waxes onto the surfaces of seedling leaves.
Citation: Li, L., . . . & Schnable, Patrick. (2013). The Maize glossy13 Gene, Cloned via BSR-Seq and SeqWalking Encodes a Putative ABC Transporter Required for the Normal Accumulation of Epicuticular Waxes. PLoS ONE, 8(12), e82333. https://doi.org/10.1371/journal.pone.0082333
Keywords: Maize; BSR-Seq; Seq-Walking; Epicuticular waxes